2017
DOI: 10.1038/s41598-017-14651-y
|View full text |Cite
|
Sign up to set email alerts
|

The role of Thyroid Transcription Factor-1 and Tumor differentiation in Resected Lung Adenocarcinoma

Abstract: To investigate the role of thyroid transcription factor-1 (TTF-1) and tumor differentiation in resected lung adenocarcinoma. A total of 520 patients with clinical early stage lung adenocarcinoma who underwent surgical resection were reviewed retrospectively. Clinical data and outcomes were evaluated with an average follow-up of 117 months. The results were validated via lung cancer cell line studies. The clinical parameters did not differ between relapse and nonrelapse patients. Exceptions were tumor different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 26 publications
2
10
0
Order By: Relevance
“…This feature is contrary to the conclusions of Zhang et al, Stenhouse et al, Zhou et al, and Yaman et al [10,11,14,15] In the present study, necrosis was a predominant feature of the TTF-1-negative group and was present in 55.66% cases while 94.33% of cases were either moderately or poorly differentiated tumors. A reciprocal correlation between tumor differentiation and TTF-1 expression has been described by Huang et al [16] Yaman et al concluded from their study that poorly differentiated tumors were generally TTF-1 negative. [15] The staining pattern of TTF-1 is largely uniform in the adenocarcinomas in spite of histologic and microenvironmental multiplicity in individual tumors.…”
Section: Discussionsupporting
confidence: 55%
“…This feature is contrary to the conclusions of Zhang et al, Stenhouse et al, Zhou et al, and Yaman et al [10,11,14,15] In the present study, necrosis was a predominant feature of the TTF-1-negative group and was present in 55.66% cases while 94.33% of cases were either moderately or poorly differentiated tumors. A reciprocal correlation between tumor differentiation and TTF-1 expression has been described by Huang et al [16] Yaman et al concluded from their study that poorly differentiated tumors were generally TTF-1 negative. [15] The staining pattern of TTF-1 is largely uniform in the adenocarcinomas in spite of histologic and microenvironmental multiplicity in individual tumors.…”
Section: Discussionsupporting
confidence: 55%
“…Therefore, patients with multi-N2 station metastasis may not benefit from the surgery because of the higher LNR although surgeons believed that each lymph node could be removed. It is undisputed that the T stage and tumor grade are significant independent predictive factors (30,31). Besides these, we found that histology also affects prognosis.…”
Section: Discussionmentioning
confidence: 60%
“…It is undisputed that the T stage and tumor grade are significant independent predictive factors ( 30 , 31 ). Besides these, we found that histology also affects prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…2). Previous studies had reported several TTF-1-negative patients with MIA in their cohorts (18,56). The exact expression profile of TTF-1 and the associated significance requires further investigation in patients with MIA.…”
Section: Discussionmentioning
confidence: 95%